Learning from The Legacy of Post-Disaster Recovery in Indonesia for The Acceleration of Post-Disaster Recovery in Lombok - Suprayoga Hadi (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2019)
As a country known for its very disaster-prone areas, Indonesia has experienced frequent disasters, either large, medium and small-scale ones, which even in the last six months have had at least a fairly large-scale natural disaster, one of which is an earthquake occurred in Lombok in late July to mid-August 2018. Learning from the experiences of post-disasters management that have occurred before, especially after the earthquake and tsunami disaster in Aceh and Nias in 2004, the earthquake in Yogyakarta in 2006, the earthquake in West Sumatra in 2009, and eruption of Mount Merapi in 2010, the post-disaster recovery process needs to be carried out in an integrated and comprehensive manner, by involving participation of stakeholders at the national and regional levels, not only the central government, local governments and other government partners. In relation to the post-earthquake recovery efforts in Lombok in 2018 which affected seven districts/cities in NTB Province which resulted in recovery needs of more than Rp. 11 trillion, despite the issuance of the Presidential Instruction policy framework Number 5 of 2018 on the Acceleration of Post-Disaster Rehabilitation and Reconstruction in NTB Province, which assigns relevant ministries/agencies and Governor and Regents and Mayors whose areas are affected in NTB Province, to be able to accelerate the process of recovering local conditions and disaster-affected communities in the affected NTB region, which for implementation still requires operational policies and strategies in the field. For this reason, some best-practices in managing the recovery process from previous disasters can be used as input in establishing appropriate and applicable policies and strategies in order to accelerate the rehabilitation and reconstruction of post-disaster areas in Lombok further, to realize a recovery to rebuild a better one, safer and more sustainable.